The Influence of Product Quality, Price Perception and Product Innovation on Purchase Decisions for Xiaomi Mobile Products at Yuli Cell, East Lampung Regency - M Jhuna Hara Asmara; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
Study This aim For analyze Influence Quality Product, Perception Price And Innovation Product to Decision Purchase Product Xiaomi cellphone at Yuli Cell, East Lampung Regency. In this research use data primary which obtained from spread questionnaire. Sample in study this as much 150 respondents with use technique probability sampling. Study this use analysis Regression Linear Multiple with using the SPSS version 23.0 program. Results study this show that there is influence positive and significant between quality product to decision purchase. There is influence positive and significant between perception prices to decision purchase. There is influence positive and significant between innovation products to decision purchase.